National Day parades : we the citizens of Singapore - Low, Annabel Hui Xin (2017)
It has been fifty years since Singapore gained independence and embarked on a journey to establish itself as a first-world country. Other than building up the economy, defence force and infrastructure of the country, the government also had to quickly commence nation-building efforts. Efforts had to be made to form a cohesive multi-racial and multi-religious society. One of the earlier nation- building practices was the celebration of National Day on August 9th every year, to commemorate the day Singapore was declared an independent nation. Since 1966, a spectacular parade has been put up every year as the highlight of the National Day celebrations. This paper seeks to argue that the National Day parade is a significant annual event that the government uses to further nation- building efforts, by evoking a sense of national identity and emotional attachment to Singapore amongst its people. This will be done through the examination of how three segments of the National Day parade – the military showcase, performances and National Day songs – have been used and adapted over the years to further the government’s nation building efforts in Singapore.